Analisis penentu biaya kesulitan keuangan - Hendi Hendi; Jessica Jessica (MBR (Management and Business Review), 2021)
Empirical studies aims to prove that the selected independent and control variables are indicators of determining the cost of financial distress. The object of research is all public companies listed on the Indonesia Stock Exchange (IDX) which are classified into 8 (eight) sectors, except for the financial sector. Data analysis uses Panel Regression analysis on secondary data samples obtained from the company's annual financial statements for the period of 2016-2020. The findings found that there is a significant negative effect between change in investment, return on assets and firm size on the cost of financial distress. The variables of probability of financial distress, holding of liquid assets, liquidity ratio, change in employment, leverage, return on equity, tobin's q, average profitability of its sector do not have a significant relationship to the cost of financial distress. Recommendations for future researchers are suggested for future research coverage not to occur during a pandemic. It is advisable for the next research to separate research that occurred during the pandemic period or the time range during normal conditions so that the sample comparison is fairer.